Implementation of Project-Based Case Method to Improve Student Problem- Solving and Creativity - Nirawana, I Wayan Sugianta; Romisa, Fahmi (Jurnal Teknologi Pendidikan : Jurnal Penelitian dan Pengembangan Pembelajaran, 2024)
Current learning is not only in the form of theory but also, in direct practice to provide students with experience that can provide them with skills in the world of work.  Problem-solving as applied to work environment also needs to be accompanied by person and team creativity. This research aims to improve the problem-solving and creativity of multimedia engineering students in videography material. The students involved in this research were class A computer education students, FKIP, Universitas Mulawarman. This type of research is classroom action research carried out over 2 cycles. The result obtained increased using case method in cycle I with an average value 78.74 to 84.24 in cycle II. Project with creativity also experienced a slight increase in the average score from 83.89 in cycle I to 84.76 in cycle II. Student responses to multimedia engineering learning using the project-based case method are positive and provide real contributions.